Sholat as Mental Health Rehabilitation for Islamic Guidance Students - Sibarani, Ramadhan Syahputra; Zainun, Zainun (Madania: Jurnal Ilmu-Ilmu Keislaman, 2025)
Mental health issues among students are a significant concern, especially when facing academic, social, and personal pressures during their studies. This research aims to explore how the practice of prayer can serve as a form of spiritual support in maintaining the mental stability of students. The research was conducted at the State Islamic University of North Sumatra (UINSU) Medan using a descriptive qualitative approach. Data was collected through in-depth interviews, observations, and documentation from seven students from various study programs aged 20-24 years. Data analysis was conducted in three stages: data reduction, data presentation, and conclusion drawing. The research results show that prayer is able to provide inner peace, reduce anxiety, and significantly improve mood. This effectiveness depends on the quality of its execution, especially if done with awareness of spiritual needs and reverence. Conversely, prayer performed solely as a formal routine without inner presence does not have a significant psychological impact. This finding implies the importance of strengthening the quality of worship as part of a holistic approach to addressing students' mental health issues.